Safety and efficacy of a new cold snare technique with clipping for colorectal angioectasia - Arimoto, Jun; Chiba, Hideyuki; Yamada, Keiji; Okada, Naoya; Kobayashi, Mikio; Kuwabara, Hiroki; Nakaoka, Michiko; Ohata, Ken (Endoscopy International Open, 2023)
Colorectal angioectasia is a major cause of lower gastrointestinal bleeding. Use of antithrombotic agents is expected to increase with aging of the population, and bleeding from angioectasia is an important issue. Although the effectiveness of endoscopic mucosal resection for colorectal angioectasia has been reported, there are no reports of cold snare technique for angioectasia (CSA). From February 2018 to February 2022, the safety of CSA was evaluated at Omori Red Cross Hospital. We investigated the incidence of bleeding (delayed post-polypectomy bleeding (DPPB) and immediate bleeding) after CSA and the incidence of rebleeding requiring repeated endoscopic treatment. During the study period, 106 angioectasias were identified during colonoscopy. We only targeted patients with bloody stools and/or anemia requiring treatment for bleeding from angioectasia. Finally, we included 11 angioectasias in this study. Rates of DPPB and rebleeding after CSA were 0 %. The rate of immediate bleeding during CSA was 27.3 % (3/11). Dilated capillaries could be observed pathologically in nine of 11 lesions (81.8 %). CSA was safe and can be a new treatment option in the future. To confirm our results and verify the long-term safety and efficacy of CSA, further studies are desirable.